Optimal Economic Growth Using Fiscal and Monetary Policies - Hassan Bougrine; Teppo A. Rakkolainen (Aboa Centre for Economics (ACE), 2009)
The literature on growth theory is rich with models attempting to explain growth differences among countries. Several variables have been proposed many of which were found to be positively related to growth. However, a major problem with these models is that the factors explaining growth are endogenously determined by their environment so that a slow-growing or a poor country will find itself helpless because all the crucial variables it has `inherited' are either deficient or inexistent. We propose policyoriented model that empowers (poor or slow-growing) countries in the sense that they can use economic policies to achieve high growth and eliminate the gap of unused productive capacity of society. We demonstrate that such objectives are possible by manipulating some key control variables, namely the rate of interest and the net government spending.
Keywords: O11; O23; H2; H3; 330; growth; maximization; fiscal policy; interest rates; deficit; money